An exploration of the role of the registered nurse in enhancing and developing the nursing skills of undergraduate nursing students in a surgical setting - Stevens, Gwynneth Roberta (Division of Nursing and Midwifery, 2015)
Registered nurses in clinical settings, through years of training combined with experience, become empowered with valuable knowledge and skills. The majority of these registered nurses are employed in public hospitals, caring for patients from culturally diverse backgrounds who face economic, psycho-social, and, in particular, physical challenges. Such conditions often provide a rich environment to undergraduate nurses for experiential learning. The experienced registered nurses, working in this rich environment, are well positioned to fulfil a crucial role in transferring, developing and enhancing skills for educating undergraduate nursing students. Their role in the development of undergraduate nursing students in the clinical environment should never be underestimated or under-utilised. The clinical environment should be considered as the most important resource for developing the confidence and competencies of undergraduate nurses. It is within this background that this research study was undertaken. The aim of this research study was to contribute to the teaching and learning roles and functions of registered nurses working in the surgical wards at the study setting in terms of teaching undergraduate nursing students. The researcher intends to make certain recommendations for the improvement of teaching and learning for undergraduate nursing students in the clinical context. In addition to exploring the feelings and perceptions of registered nurses regarding their teaching role, the minor dissertation seeks to explore some of the misconceptions and challenges relating to the nature, extent and responsibilities of this teaching role. I therefore set out to answer the following research question: â€œHow do registered nurses at a Western Cape academic hospital perceive their teaching and learning role as clinical teachers?â€